Vidareutveckling av metod för bedömning av miljöpåverkan i samhällsekonomiska analyser vid investeringar i det svenska elstamnätet - Andersson, Elinda (2016)
Svenska kraftnät, which is the authority responsible for the Swedish national grid, performs cost-benefit analysis (CBA) to assess which of different investment projects that are of greatest benefit to society. The environmental impacts are also estimated during this analysis. In this paper, a tool for estimating the environmental impacts during the lifetime of a grid component has been developed with the purpose of enabling a more complete environmental evaluation. A life cycle assessment was performed to develop the tool. The impact categories that have been studied are climate change (kg CO2-eq), freshwater eutrophication (kg P-eq), particulate matter formation (kg PM10-eq) and terrestrial acidification (kg SO2-eq). To be able to compare the environmental effects with other costs and benefits in the CBA a monetary valuation of the impact categories has been established. The result of this paper indicates that the AC-overhead line is the technology that contributes with the lowest environmental impact during the life cycle. This result, however, is obtained when analyzing different technical alternatives with the same preconditions, which rarely is the case in real projects. The result can therefore differ between different investment projects. The tool enables an assessment of the environmental impacts of different investment projects in the Swedish national grid, and is therefore an important part of the cost-benefit analysis to determine which alternative is best suited.